Depression and somatization in Turkish migrants in Germany: the role of migration-related stressors - Hanewald, Bernd; Hahn, Eric; Ta, Tam Thi Minh; Elguen, Yasemin; Stingl, Markus (Frontiers in Psychiatry, 2025)
IntroductionMigration-related stressors (MRS), such as loss, cultural conflict, and language barriers, are linked to increased psychological distress. This study investigates the impact of MRS on de-pressive symptoms and somatization among Turkish-speaking first-generation migrants in Germany.MethodIn a cross-sectional study, 60 psychiatric outpatients completed standardized measures as-sessing MRS, depressive symptoms (BDI-II), and somatization (PHQ-15). Regression analy-ses controlled for age, gender, and socioeconomic status.ResultsHigher MRS significantly predicted both depressive symptoms and somatization. Somatic complaints were particularly associated with language difficulties, separation experiences, and intergenerational value conflicts.ConclusionFindings support the need to integrate cultural humility—defined as clinician self-awareness, openness, and contextual sensitivity—into evidence-based care. Symptom interpretation must consider patients’ migration histories and cultural frameworks. Culturally adapted, person-centered interventions may improve diagnostic accuracy and treatment outcomes for migrant populations.